Impact of GA3 on Sugar and Lipid Degradation during Annona x atemoya Mabb. Seed Germination - Mimi, Carolina Ovile [UNESP]; Sousa, Marília Caixeta [UNESP]; Corrêa, Patrícia Luciana Carriel [UNESP]; De-la-Cruz-Chacón, Ivan; Boaro, Carmen Sílvia Fernandes [UNESP]; Ferreira, Gisela [UNESP] (My University, 2023)
Gibberellins act to overcome dormancy and increase the germination rate of seeds of several species, including the genus Annona. Considering that Annona seeds have a high lipid content and have few sugars, the degradation of such reserves from the application of gibberellins has not been described so far. This study aimed to evaluate how the application of different gibberellic acid (GA3) concentrations acts on the sugar and lipid degradation pattern during the germination of atemoya seeds (Annona x atemoya Mabb.). Therefore, two experiments were carried out, one to evaluate the effect of GA3 on the germination process and another to evaluate the degradation of the reserves. To study the effect of GA3 on germinability, four treatments with GA3 concentrations of 0, 250, 500, and 1000 mg L−1 were used. To study the degradation of reserves, the four GA3 concentrations and five collection times were used (dry seed; seed with 1 day, 5 days, and 10 days of water acquisition; and seeds with primary root emission). Atemoya seeds showed an increase in germinability and changes in the sugar and lipid degradation pattern during the germination process in response to the treatments with GA3. Lipid and sugar degradation was observed from 24 h after seed immersion in GA3. The highest GA3 concentrations (500 and 1000 mg L−1) led to increases of 25% and 20%, respectively, in the germination rate, intensification of lipid degradation in seeds with primary root emission, and a decrease in sugar concentration until the 5th day.
Keywords: Annona; germination; gibberellins; lipids; reserve mobilization; sugars